Suppression of head and neck cancer cell survival and cisplatin resistance by GRP78 small molecule inhibitor YUM70 - Yamamoto, Vicky; Wang, Bintao; Lee, Amy S. (Frontiers in Oncology, 2023)
Background Head and neck squamous cell carcinoma (HNSCC) is one of the leading causes of cancer-related death worldwide. Surgical resection, radiation and chemotherapy are the mainstay of HNSCC treatment but are often unsatisfactory. Cisplatin is a commonly used chemotherapy in HNSCC; however, cisplatin resistance is a major cause of relapse and death. The 78-kD glucose-regulated protein (GRP78) is the master regulator of the unfolded protein response (UPR) and is implicated in therapeutic resistance in cancer. The role of GRP78 in cisplatin resistance in HNSCC remains unclear. YUM70 is a newly discovered hydroxyquinoline analogue and found to be an inhibitor of GRP78. The effect of YUM70 in HNSCC cell lines is unknown. Method Knockdown of GRP78 by siRNAs was performed to investigate the effect of GRP78 reduction in endoplasmic reticulum (ER)-stress induced and general apoptosis. Western blots examining apoptotic markers were performed on three HPV-negative HNSCC cell lines. WST-1 assay was performed to determine cell viability. In reverse, we utilized AA147, an ER proteostasis regulator to upregulate GRP78, and apoptotic markers and cell viability were determined. To test the ability of YUM70 to reverse cisplatin resistance, cisplatin-resistant HNSCC cell lines were generated by prolonged, repeated exposure to increasing concentrations of cisplatin. Colony formation assay using the cisplatin-resistant HNSCC cell line was performed to assess the in vitro reproductive cell survival. Furthermore, to test the ability of YUM70 to reverse cisplatin resistance in a physiologically relevant system, we subjected the 3D spheroids of the cisplatin-resistant HNSCC cell line to cisplatin treatment with or without YUM70 and monitored the onset of apoptosis. Results Reduction of GRP78 level induced HNSCC cell death while GRP78 upregulation conferred higher resistance to cisplatin. Combined cisplatin and YUM70 treatment increased apoptotic markers in the cisplatin-resistant HNSCC cell line, associating with reduced cell viability and clonogenicity. The combination treatment also increased apoptotic markers in the 3D spheroid model. Conclusion The GRP78 inhibitor YUM70 reduced HNSCC cell viability and re-sensitized cisplatin-resistant HNSCC cell line in both 2D and 3D spheroid models, suggesting the potential use of YUM70 in the treatment of HNSCC, including cisplatin-resistant HNSCC.